Genome-wide analyses provide insights into genetic variation, phylo- and co-phylogenetic relationships, and biogeography of the entomopathogenic nematode genus Heterorhabditis - Machado, Ricardo A R; Muller, Arthur; Hiltmann, Alexandre; Bhat, Aashaq Hussain; Půža, Vladimír; Malan, Antoinette P; Castaneda-Alvarez, Carlos; San-Blas, Ernesto; Duncan, Larry W; Shapiro-Ilan, David; Karimi, Javad; Lalramliana; et al. (Molecular phylogenetics and evolution, 2025)
Multigene, genus-wide phylogenetic studies have uncovered the limited taxonomic resolution power of commonly used gene markers, particularly of rRNA genes, to discriminate closely related species of the nematode genus Heterorhabditis. In addition, conflicting tree topologies are often obtained using the different gene markers, which limits our understanding of the phylo- and co-phylogenetic relationships and biogeography of the entomopathogenic nematode genus Heterorhabditis. Here we carried out phylogenomic reconstructions using whole nuclear and mitochondrial genomes, and whole ribosomal operon sequences, as well as multiple phylogenetic reconstructions using various single nuclear and mitochondrial genes. Using the inferred phylogenies, we then investigated co-phylogenetic relationships between Heterorhabditis and their Photorhabdus bacterial symbionts and biogeographical patterns. Robust, well-resolved, and highly congruent phylogenetic relationships were reconstructed using both whole nuclear and mitochondrial genomes. Similarly, whole ribosomal operon sequences proved valuable for phylogenomic reconstructions, though they have limited value to discriminate closely related species. In addition, two mitochondrial genes, the cytochrome c oxidase subunit I (cox-1) and the NADH dehydrogenase subunit 4 (nad-4), and two housekeeping genes, the fanconi-associated nuclease 1 (fan-1) and the serine/threonine-protein phosphatase 4 regulatory subunit 1 (ppfr-1), provided the most robust phylogenetic reconstructions compared to other individual genes. According to our findings, whole nuclear and/or mitochondrial genomes are strongly recommended for reconstructing phylogenetic relationships of the genus Heterorhabditis. If whole nuclear and/or mitochondrial genomes are unavailable, a combination of nuclear and mitochondrial genes can be used as an alternative. Under these circumstances, sequences of multiple conspecific isolates in a genus-wide phylogenetic context should be analyzed to avoid artefactual species over-splitting driven by the high intraspecific sequence divergence of mitochondrial genes and to avoid artefactual species lumping driven by the low interspecific sequence divergence of some nuclear genes. On the other hand, we observed that the genera Heterorhabditis and Photorhabdus exhibit diverse biogeographic patterns, ranging from cosmopolitan species to potentially endemic species, and show high phylogenetic congruence, although host switches have also occurred. Our study contributes to a better understanding of the biodiversity and phylo- and co-phylogenetic relationships of an important group of biological control agents and advances our efforts to develop more tools that are compatible with sustainable and eco-friendly agricultural practices.
Keywords: Biological control; Phylogenetics; Strongyloidea; Cell Nucleus; genetická variace; fylogeneze; Phylogenetic species concept; Phylogeny; Molecular systematics; Phylogenomics; Genome-Wide Association Study; buněčné jádro; Phylogeography; pravděpodobnostní funkce; genom mitochondriální; Genome, Mitochondrial; Likelihood Functions; Animals; Genome, Helminth; genom u helmintů; Taxonomy; zvířata; fylogeografie; Genetic Variation; Sustainable agriculture; celogenomová asociační studie